Shari'ah principles in tourism and hospitality services: a Malaysian perspective - Abas, Afridah; Ramli, Noriah; Mohd Daud, Noor Najihah (Malaysian Journal of Consumer and Family Economics, 2017)
Muslim friendly tourism and hospitality is an emerging sector in the Malaysian and global halal industry. This effort aims at fulfilling the needs of local and international Muslim tourists. There have been various efforts made by service providers in the hospitality services industry to fulfil the needs of Muslim tourists and this includes providing halal inflight food, Muslim friendly tourism package, Muslim friendly tourism products and Muslim friendly tourism accommodation. In the latesLdevelopment, effort is also made to provide Muslim friendly transportation. This article aims to highlight the Shari'ah compliant principles in tourism and hospitality services in Malaysia as manifested in the Malaysian Standard MS 2610: 2015 for Muslim Friendly Hospitality Services Requirements. It is hoped that the article could better explain how the guideline could be applied by ser'v'ice providers who are interested in preparing themselves for a more Shari'ah compliant hospitality service in the tourism sector.